MAYBE Initial complexity problem: 1: T: (?, 1) f0(a, b, c, d) -> f3(a, e, c, d) [ a >= 10 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ 9 >= a ] (?, 1) f1(a, b, c, d) -> f0(-1, b, c, -1) [ 9 >= a ] (1, 1) f2(a, b, c, d) -> f0(0, b, c, d) start location: f2 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ 9 >= a ] (?, 1) f1(a, b, c, d) -> f0(-1, b, c, -1) [ 9 >= a ] (1, 1) f2(a, b, c, d) -> f0(0, b, c, d) start location: f2 leaf cost: 1 Testing for reachability in the complexity graph removes the following transition from problem 2: f1(a, b, c, d) -> f0(-1, b, c, -1) [ 9 >= a ] We thus obtain the following problem: 3: T: (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ 9 >= a ] (1, 1) f2(a, b, c, d) -> f0(0, b, c, d) start location: f2 leaf cost: 1 Applied AI with 'oct' on problem 3 to obtain the following invariants: For symbol f0: -X_1 >= 0 This yielded the following problem: 4: T: (1, 1) f2(a, b, c, d) -> f0(0, b, c, d) (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(0, b, c, d) with all transitions in problem 4, the following new transition is obtained: f2(a, b, c, d) -> f0(-1, b, 0, d) [ 0 >= 0 /\ 9 >= 0 ] We thus obtain the following problem: 5: T: (1, 2) f2(a, b, c, d) -> f0(-1, b, 0, d) [ 0 >= 0 /\ 9 >= 0 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-1, b, 0, d) [ 0 >= 0 /\ 9 >= 0 ] with all transitions in problem 5, the following new transition is obtained: f2(a, b, c, d) -> f0(-2, b, -1, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 ] We thus obtain the following problem: 6: T: (1, 3) f2(a, b, c, d) -> f0(-2, b, -1, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-2, b, -1, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 ] with all transitions in problem 6, the following new transition is obtained: f2(a, b, c, d) -> f0(-3, b, -2, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 ] We thus obtain the following problem: 7: T: (1, 4) f2(a, b, c, d) -> f0(-3, b, -2, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-3, b, -2, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 ] with all transitions in problem 7, the following new transition is obtained: f2(a, b, c, d) -> f0(-4, b, -3, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 ] We thus obtain the following problem: 8: T: (1, 5) f2(a, b, c, d) -> f0(-4, b, -3, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-4, b, -3, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 ] with all transitions in problem 8, the following new transition is obtained: f2(a, b, c, d) -> f0(-5, b, -4, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 ] We thus obtain the following problem: 9: T: (1, 6) f2(a, b, c, d) -> f0(-5, b, -4, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-5, b, -4, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 ] with all transitions in problem 9, the following new transition is obtained: f2(a, b, c, d) -> f0(-6, b, -5, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 ] We thus obtain the following problem: 10: T: (1, 7) f2(a, b, c, d) -> f0(-6, b, -5, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-6, b, -5, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 ] with all transitions in problem 10, the following new transition is obtained: f2(a, b, c, d) -> f0(-7, b, -6, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 ] We thus obtain the following problem: 11: T: (1, 8) f2(a, b, c, d) -> f0(-7, b, -6, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-7, b, -6, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 ] with all transitions in problem 11, the following new transition is obtained: f2(a, b, c, d) -> f0(-8, b, -7, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 ] We thus obtain the following problem: 12: T: (1, 9) f2(a, b, c, d) -> f0(-8, b, -7, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-8, b, -7, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 ] with all transitions in problem 12, the following new transition is obtained: f2(a, b, c, d) -> f0(-9, b, -8, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 ] We thus obtain the following problem: 13: T: (1, 10) f2(a, b, c, d) -> f0(-9, b, -8, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-9, b, -8, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 ] with all transitions in problem 13, the following new transition is obtained: f2(a, b, c, d) -> f0(-10, b, -9, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 ] We thus obtain the following problem: 14: T: (1, 11) f2(a, b, c, d) -> f0(-10, b, -9, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-10, b, -9, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 ] with all transitions in problem 14, the following new transition is obtained: f2(a, b, c, d) -> f0(-11, b, -10, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 ] We thus obtain the following problem: 15: T: (1, 12) f2(a, b, c, d) -> f0(-11, b, -10, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-11, b, -10, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 ] with all transitions in problem 15, the following new transition is obtained: f2(a, b, c, d) -> f0(-12, b, -11, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 /\ 11 >= 0 /\ 9 >= -11 ] We thus obtain the following problem: 16: T: (1, 13) f2(a, b, c, d) -> f0(-12, b, -11, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 /\ 11 >= 0 /\ 9 >= -11 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-12, b, -11, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 /\ 11 >= 0 /\ 9 >= -11 ] with all transitions in problem 16, the following new transition is obtained: f2(a, b, c, d) -> f0(-13, b, -12, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 /\ 11 >= 0 /\ 9 >= -11 /\ 12 >= 0 /\ 9 >= -12 ] We thus obtain the following problem: 17: T: (1, 14) f2(a, b, c, d) -> f0(-13, b, -12, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 /\ 11 >= 0 /\ 9 >= -11 /\ 12 >= 0 /\ 9 >= -12 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-13, b, -12, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 /\ 11 >= 0 /\ 9 >= -11 /\ 12 >= 0 /\ 9 >= -12 ] with all transitions in problem 17, the following new transition is obtained: f2(a, b, c, d) -> f0(-14, b, -13, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 /\ 11 >= 0 /\ 9 >= -11 /\ 12 >= 0 /\ 9 >= -12 /\ 13 >= 0 /\ 9 >= -13 ] We thus obtain the following problem: 18: T: (1, 15) f2(a, b, c, d) -> f0(-14, b, -13, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 /\ 11 >= 0 /\ 9 >= -11 /\ 12 >= 0 /\ 9 >= -12 /\ 13 >= 0 /\ 9 >= -13 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 By chaining the transition f2(a, b, c, d) -> f0(-14, b, -13, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 /\ 11 >= 0 /\ 9 >= -11 /\ 12 >= 0 /\ 9 >= -12 /\ 13 >= 0 /\ 9 >= -13 ] with all transitions in problem 18, the following new transition is obtained: f2(a, b, c, d) -> f0(-15, b, -14, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 /\ 11 >= 0 /\ 9 >= -11 /\ 12 >= 0 /\ 9 >= -12 /\ 13 >= 0 /\ 9 >= -13 /\ 14 >= 0 /\ 9 >= -14 ] We thus obtain the following problem: 19: T: (1, 16) f2(a, b, c, d) -> f0(-15, b, -14, d) [ 0 >= 0 /\ 9 >= 0 /\ 1 >= 0 /\ 9 >= -1 /\ 2 >= 0 /\ 9 >= -2 /\ 3 >= 0 /\ 9 >= -3 /\ 4 >= 0 /\ 9 >= -4 /\ 5 >= 0 /\ 9 >= -5 /\ 6 >= 0 /\ 9 >= -6 /\ 7 >= 0 /\ 9 >= -7 /\ 8 >= 0 /\ 9 >= -8 /\ 9 >= -9 /\ 10 >= 0 /\ 9 >= -10 /\ 11 >= 0 /\ 9 >= -11 /\ 12 >= 0 /\ 9 >= -12 /\ 13 >= 0 /\ 9 >= -13 /\ 14 >= 0 /\ 9 >= -14 ] (?, 1) f0(a, b, c, d) -> f0(a - 1, b, a, d) [ -a >= 0 /\ 9 >= a ] start location: f2 leaf cost: 1 Complexity upper bound ? Time: 0.853 sec (SMT: 0.791 sec)